(untitled) (Research, Society and Development, 2021)
This study was undertaken to evaluate the effects of different row spacings and planting populations on dry matter yield, nutritive value, and predicted milk yield of BRS 658 forage sorghum hybrid growing in Brazilian conditions. A late relative maturity forage sorghum [Sorghum bicolor (L.) Moench; 110 d-115d to soft dough stage; BRS 658 – Embrapa] was planted at 3 row spacing (0.5, 1.0 and 1.5 m) and at 3 planting population (50 x 103, 100 x 103, and 150 x 103 plants.ha-1). Treatments were arranged in a randomized complete block design in a 3 x 3 factorial arrangement, using 4 replicate plots per row spacing x plant population combination. At harvest, weights of whole-plant sorghum forage were obtained to calculate DM yields. Chemical composition was assessed by performing wet chemistry analysis. Plant height, stem diameter, and harvest were performed 110 days after sowing (DAS). Estimated milk yield per unit of forage and per hectare were calculated using Milk2006. Summative equations were used to predict TDN and NEL. Yield of wet and DM forage sorghum exhibited a negative quadratic response as row spacing increased, reaching the maximum yield response at row spacing of 1.23m and 1.22m, respectively. In addition, negative linear effect was detected for both wet and DM sorghum forage yield as planting density increased. Regarding agronomic measurements, sorghum height exhibited a negative linear pattern as plant density increased. Otherwise, stem diameter increased as planting density increased. Whole-plant sorghum forage DM content decreased linearly with increasing planting density. Conversely, ashes increased linearly as planting density increased. Neutral detergent insoluble protein exhibited a positive quadratic effect with increasing planting density, reaching the minimum value when planting density was 104.2 x 103 plants.ha-1. Finally, a negative quadratic effect for predicted milk yield per hectare was also observed with increasing row spacing, whereas the maximum milk yield per hectare value was detected when row spacing was 1.20m. In conclusion, taking into account a subtropical climate, the ideal row spacing and planting density recommendation for a high yield and nutritional quality sorghum forage are 1.2 m and 104 x 103 plants.ha-1, respectively.